Success fee agreements in Scotland : a consultation on Part 1 of the Civil Litigation (Expenses and Group Proceedings) (Scotland) Act 2018 : analysis of consultation responses /: a consultation on Part 1 of the Civil Litigation (Expenses and Group Proceedings) (Scotland) Act 2018 : analysis of consultation responses. (2019) - Unknown
No abstract available